2021
DOI: 10.1021/acssynbio.1c00161
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic Macrocyclic Lipo-lanthipeptides Display Antimicrobial Activity Against Bacterial Pathogens

Abstract: A large number of antimicrobial peptides depend on intramolecular disulfide bonds for their biological activity. However, the relative instability of disulfide bonds has limited the potential of some of these peptides to be developed into therapeutics. Conversely, peptides containing intramolecular (methyl)lanthionine-based bonds, lanthipeptides, are highly stable under a broader range of biological and physical conditions. Here, the class-II lanthipeptide synthetase CinM, from the cinnamycin gene cluster, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…(iii) The deep knowledge of the RSP biosynthetic rules to engineer and produce antimicrobials with improved efficiency, such as recently shown with semi-synthesized lipo-lanthipeptides. 267…”
Section: Current Standpoints To Future Directions: From Microbial Eco...mentioning
confidence: 99%
“…(iii) The deep knowledge of the RSP biosynthetic rules to engineer and produce antimicrobials with improved efficiency, such as recently shown with semi-synthesized lipo-lanthipeptides. 267…”
Section: Current Standpoints To Future Directions: From Microbial Eco...mentioning
confidence: 99%
“…CinA binding (Figure and Figure S20) triggers a further organization in the capping domain (peptides D42-L56, A109-L118, and E196-E204), motif 1 (D225-L230), and in several dehydratase active site peptides containing catalytic residues involved in phosphoryl transfer (D402, H404, and N407) . Alanine mutational scanning of CinA localized the CinM binding site to an element near the N terminus of the CinA leader peptide (CinA residues V11-A17) . This segment of the CinA leader peptide is predicted by AlphaFold to interact directly with the D42-L56 helical element of the CinM capping domain (Figure and Figure S33).…”
Section: Resultsmentioning
confidence: 99%
“…29 Alanine mutational scanning of CinA localized the CinM binding site to an element near the N terminus of the CinA leader peptide (CinA residues V11-A17). 56 This segment of the CinA leader peptide is predicted by AlphaFold to interact directly with the D42-L56 helical element of the CinM capping domain (Figure 5 and Figure S33). Similar to all the other LanMs investigated here, additional interactions are predicted by AlphaFold between the helical region at the C terminus of the CinA leader peptide and the CinM kinase activation domain, which also becomes organized in the [CinM:CinA] complex (motif 4, peptide A569-E586, Figures 5 and 6).…”
Section: Generalmentioning
confidence: 99%
“…(C) After chemical handles have been installed, functional groups such as fatty acid chains can be added to the ring A construct to obtain the intended functionality. 20 (D) Linear peptides can be added to the minimal ring a construct in a ribosomal way to obtain lanthionine-stabilized linear peptides.…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been shown that by adding functional groups, for example, fatty acid chains, to otherwise nonactive lanthipeptides, good antimicrobial activity can be obtained. 20 Lanthipeptides or fragments thereof, can in this sense, be used as a stable module to which all kinds of modifications can be added in vitro. The proposed ring A module could be obtained through the incorporation of noncanonical amino acids that have convenient chemical handle side chains.…”
Section: Introductionmentioning
confidence: 99%